On the Prosocial Behavior of Students in Daily Life and Evaluation Analysis (Asian Education Studies, 2022)
Are students' prosocial behaviors developed in knowledge learning and skill teaching under the background of college education? Through the observation of prosocial behavior of students in daily life, this paper expounds the content and measures we should analyze as educators.